KEBIJAKAN ANTI DUMPING UNI EROPA TERHADAP BAJA COLD ROLLED STAINLESS STEEL (CRSS) INDONESIA TAHUN 2021-2022 - Yulian, Arla Tri; Fuadi, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The focus of this research is to analyze the European Union's anti-dumping policy on Cold Rolled Stainless Steel products from Indonesia in 2021-2022. During the investigation period, the European Committee discovered dumping practices on Cold Rolled Stainless Steel imported from Indonesia and that there were losses to the European Union steel industry. The form of loss experienced by European Union steel producers is the loss of market share, due to the increasing price competitiveness of imported products which the European Union sees as an intervention by the Indonesian government. This research uses a qualitative descriptive method, with a nation-state level of analysis, the theory used is protectionism theory from a neo-mercantilism perspective. To analyze this case, the author collected data from journals, books, websites, and other sources related to the European Union-Indonesia requirements and inspections of the export of Indonesian Cold Rolled Stainless Steel steel products. The results of this research show that the European Union's anti-dumping policy towards Indonesian Cold Rolled Stainless Steel is to impose countervailing measures in the form of anti-dumping import duties (BMAD) on imported products from Indonesia. The Indonesian government provides interventions that favor domestic producers in the form of HGBT policies, investment incentives, protection of import permits through regulations, prohibition and restriction policies (lartas), as well as the implementation of Indonesian National Standards (SNI). Therefore, the selling price of steel in Indonesia is cheaper than the selling price of steel in European Union countries. Therefore, the existence of anti-dumping import duties affects Indonesian steel producers when they sell their steel, this problem resulted in a WTO panel being sued by Indonesia. Keywords: Anti Dumping Import Duty (BMAD), Cold Rolled Stainless Steel, Dumping, Indonesia, European Union, Proteksionisme.